SIFO 1987: Industry managers about the environment - Swedish Institute of Public Opinion Research; Federation of Swedish Industries (Swedish Institute of Public Opinion Research, 1993)
The Swedish Institute of Public Opinion Research (SIFO) carried out this survey at the request of the Federation of Swedish Industries. Questions were asked about environmental commitments and topicality of environmental issues within the company, personnel responsible for environmental issues and the importance of environmental aspects when developing new technology and new products. The managers also had to mention the major environmental problem of the company at present and within the next two years, if the company had any permissions for industrial emissions and plans for decreasing these emissions. Furthermore the respondents were asked about their confidence in institutions within the environmental sphere, environmental activists and journalist. There were also a number of questions dealing with the opinion on the way the Federation of Swedish Industries acts in environmental issues. Background variables include information on number of employees, turnover and trade association.

Svenska institutet för opinionsundersökningar (SIFO) genomförde denna undersökning på begäran av Industriförbundet. Frågor ställdes om miljöåtaganden och aktuella miljöfrågor inom företaget, personligt ansvar för miljöfrågor och vikten av miljöaspekter när man utvecklar ny technologi och nya produkter. Cheferna måste också ange de största miljöproblemen som finns i företaget i både nutid och inom de närmsta två åren, om företaget hade några utsläppsrättigheter samt vilka planer det finns för att minska utsläppen. Vidare ställdes de svarande frågan om de hade förtroende för institutioner inom miljöområdet, miljöaktivister och journalister. Det fanns också ett antal frågor som handlade om uppfattningen om sättet Industriförbundet agerar i miljöfrågor. Bakgrundsvariabler inkluderar information om antalet anställda, omsättning och branschorganisationer.
SIFO 1987: Industrins chefer om miljön
Keywords: Environment and conservation; Miljö och naturvård; Business/industrial management and organisation; Företags-/industriledning och organisation; Social Sciences; Samhällsvetenskap